Pushing the Boundaries of the Social:Private Agri-food Standards and the Governance of Fair Trade in European Public Procurement - Fisher, Eleanor; Sheppard, Hannah (The International Journal of Sociology of Agriculture and Food, 2013)
This article examines how fair trade and associated private standards are integrated into European public procurement. Procurement law is guided by principles of equity, non-discrimination, and transparency; one consequence is that legal obstacles exist to fair trade being privileged within public purchasing. Taking an agency-based approach, evidence from Wales reveals how fair trade’s passage into procurement practice is negotiated and legal risk framed by different actors. This process exposes contestations over values that reflect wider dynamics between global civil society activism, public management bureaucracies, and neo-liberal rationales. Focusing on processes of governability, it is argued that there is a need to keep agency, power and knowledge in view within the dynamics of local transformation, rather homogenizing these dimensions as part of a technical process. Pushing the boundaries of the social in public procurement reveals how practices and knowledge on ethical consumption enter into a new governance arena within the global agri-food system.